DO LEARNERS COLLABORATE DURING TASK PERFORMANCE? - Naashia Mohamed (Universitas Katolik Indonesia Atma Jaya, 2006)
The research based on sociocultural theory suggests that studying learner interaction during task performance will provide a window for understanding the cognitive processes that are involved in acquiring a second language. The study reported here investigated the extent to which pairs of learners collaborated in performing rule-discovery grammar tasks. It took into account the proportion of contribution each learner made to the task and the type of scaffolded assistance they provided each other. The findings indicate that learners do generally collaborate while performing tasks, often sharing talk equally and with little indication of a dominant partner. The interaction between the learners of all pairs investigated in the study displayed evidence of scaffolding in various forms, indicating that they generally approached the tasks with a mutual, collaborative orientation. Learners adopted the roles of experts and novices, which were at times interchangeable, and helped each other to arrive at a shared solution. Keywords: sociocultural theory, task performance, rule-discovery grammar tasks, scaffolded assistance